MENGGUGAT FENOMENA EKSPLOITASI IKAN HIU DENGAN PENDEKATAN LITERASI KRITIS DI SEKOLAH DASAR - Rengganis, Ira; Ibrahim, Teguh; Darmayanti, Mela; Juwita, Winda Marlina (Universitas Pendidikan Indonesia, 2019)
Abstract: The purpose of this study is to provide an understanding of how critical literacy-based learning practices can be implemented in elementary schools by raising the issue of exploitation of nature. The practice of critical literacy-based learning in this study uses an educational model with problems whose philosophical basis derives from the critical pedagogic of Paulo Freire. The concept of education seeks to deal with humans on problematic phenomena that disturb the balance of life to be addressed critically. The phenomenon that will be sued is